SGLT2 inhibitors for patients with type 2 diabetes and CKD: a narrative review - Merlin C. Thomas; Brendon L. Neuen; Stephen M. Twigg; Mark E. Cooper; Sunil V. Badve (2023)
Sodium‐glucose co-transporter 2 (SGLT2) inhibitors have recently emerged as an effective means to protect kidney function in people with type 2 diabetes and chronic kidney disease (CKD). In this review, we explore the role of SGLT2 inhibition in these individuals. SGLT2 inhibitors specifically act to inhibit sodium and glucose reabsorption in the early proximal tubule of the renal nephron. Although originally developed as glucose-lowering agents through their ability to induce glycosuria, it became apparent in cardiovascular outcome trials that the trajectory of kidney function decline was significantly slowed and the incidence of serious falls in kidney function was reduced in participants receiving an SGLT2 inhibitor. These observations have recently led to specific outcome trials in participants with CKD, including DAPA-CKD, CREDENCE and EMPA-KIDNEY, and real-world studies, like CVD-REAL-3, that have confirmed the observation of kidney benefits in this setting. In response, recent KDIGO Guidelines have recommended the use of SGLT2 inhibitors as first-line therapy in patients with CKD, alongside statins, renin–angiotensin–aldosterone system inhibitors and multifactorial risk factor management as indicated. However, SGLT2 inhibitors remain significantly underutilized in the setting of CKD. Indeed, an inertia paradox exists, with patients with more severe disease less likely to receive an SGLT2 inhibitor. Concerns regarding safety appear unfounded, as acute kidney injury, hyperkalaemia, major acute cardiovascular events and cardiac death in patients with CKD appear to be lower following SGLT2 inhibition. The first-in-class indication of dapagliflozin for CKD may begin a new approach to managing kidney disease in type 2 diabetes.